The Moderate Effect of Audit Committee Independence on the Board Structure and Real Earnings Management: Evidence from Jordan - DAKHLALLH, MOHAMMAD MUSTAFA; RASHID, NORFADZILAH; ABDULLAH, WAN AMALINA WAN; SHEHAB, HOSSAM JAMIL AL (The journal of contemporary issues in business and government, 2021)
The current study aimed to explore the moderate effected of independence of the audit committee on the connection between board structure (i.e. size, independence and CEO duality) and real earnings management (REM) in listed companies in Jordan. The current study covered 910 firm-year observations of the industrial and service sector listed companies in the Amman Stock Exchange (ASE) from 2009 to 2018. Using the Fixed Effect approach, the results of the data analysis show a negative and significant impact of board size and CEO duality on REM. There was, however, a significant positive correlation between board independence and REM. In general, the findings showed that the structure of the board is a determinant of REM. In the case of the moderate effect, found the audit committee independence have moderately affected the relationship between board structure and REM. In short, the findings of this study indicate that the moderate effect of audit committee independence weakens the effect of board size and CEO duality on the determination of REM while increasing the effectiveness of board independence to control of REM. Furthermore, the findings of the current study have significant implications for audit practitioners, policymakers, investors and regulators in their efforts to limit REM activities and increase the quality of Jordanian firms’ financial reporting.